SPARC: Igniting Change in Scholarly Communication - Baker, Shirley K. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
I am speaking today about the current state of SPARC, the Scholarly Publishing and Academic Resources Coalition, initiative of the Association of Research Libraries. I am titling my presentation Igniting Change in Scholarly Communication, because that is what has happened. When SPARC was formed, Ken Frazier, the engine behind its formation, said that a spark could be two things: something easily extinguished or the cause of a conflagration. We are delighted and proud to say that this SPARC seems to have ignited a conflagration. Your inviting us here to talk about SPARC is evidence of that.